2019
DOI: 10.1002/cyto.a.23844
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Flow Cytometric Immunophenotyping for Hematological Malignancies: The FranceFlow Group Experience

Abstract: Flow cytometry is broadly used for the identification, characterization, and monitoring of hematological malignancies. However, the use of clinical flow cytometry is restricted by its lack of reproducibility across multiple centers. Since 2006, the EuroFlow consortium has been developing a standardized procedure detailing the whole process from instrument settings to data analysis. The FranceFlow group was created in 2010 with the intention to educate participating centers in France about the standardized inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Sophisticated 8–10 colour flow cytometry is at the basis of the diagnosis, characterisation and monitoring of haematological malignancies. Correct implementation of the technique and standardisation in its applications is of high importance and several guidelines to achieve this have recently been published 22,23 . In this study, we demonstrate that harmonisation between flow‐cytometers is required for comparable results.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Sophisticated 8–10 colour flow cytometry is at the basis of the diagnosis, characterisation and monitoring of haematological malignancies. Correct implementation of the technique and standardisation in its applications is of high importance and several guidelines to achieve this have recently been published 22,23 . In this study, we demonstrate that harmonisation between flow‐cytometers is required for comparable results.…”
Section: Discussionmentioning
confidence: 67%
“…Correct implementation of the technique and standardisation in its applications is of high importance and several guidelines to achieve this have recently been published. 22,23 In this study, we demonstrate that harmonisation between flow-cytometers is required for comparable results. Here, the use of BD's FC beads or setup according to Euroflow protocol was adequate to result in comparable measurements as percentages of lymphocytes, blasts, CD34 + blasts, CD34 + CD38 dim and CD34 + CD38fractions were decidedly comparable among all institutes (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…Previous experience within EuroFlow demonstrated that subsequent training of centers with higher percentage of checks/alarms show decrease number of alarms. Strong compliance to the instrument setup and sample processing SOPs are thereby of utmost importance for appropriate use of both the AGI tools and database-guided diagnostic orientation toward the most appropriate subsequent AL panel, and should be verified with already existing quality controls and the local average number of checks [24][25][26][27]. Of note, the use of validated alternative reagents, like the OneFlow ALOT and the Cytognos ALOT kits, resulted in highly comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the EuroFLOW consortium has developed a standardized procedure detailing the entire process from instrument settings to data analysis, including tools to process large data files in diagnostic laboratories (58,59). EuroFLOW standards are commonly considered a robust approach (61,62). These included issues related to operator/center expertise and training, panel design, data analysis and interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…These included issues related to operator/center expertise and training, panel design, data analysis and interpretation of results. EuroFLOW standards are commonly considered a robust approach (61,62). Minimum standards have also been defined in the setting of flow cytometry SRLs, providing guidance for best practices in instrumentation, training, experimental design, biosafety standards, and sample handling (11,20,21).…”
Section: Discussionmentioning
confidence: 99%